Peran Intensi Berwirausaha dan Kecerdasan Emosional Pengaruhnya Terhadap Kepercayaan Diri dan Motivasi Berwirausaha Mahasiswa - Sahabuddin, Romansyah; Azhari, Azlan; Burhamzah, Rahmat (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
The purpose of this study was to analyze the relationship of entrepreneurial intention and emotional quotient on the effect on self efficacy and entrepreneurial motivation of students. This research was conducted at the Management Study Program, Faculty of Economics and Business, Universitas Negeri Makassar. The total population of 2021 students is 409. The number of samples is determined using the Slovin equation and is known to be 202 students in the class of 2021 who are in nine study group classes. Data collection techniques using questionnaires, observation and interview techniques. The analytical tool used to answer the hypothesis in this study is Structural Equation Modeling analysis.